Not quite Snow White - Franklin, Ashley; Glenn, Ebony (New York : Harper, 2019)
Once upon a time, there was a girl who wanted nothing more than to play Snow White in her school's musical. Excitedly, Tameika dances and sings her way through the halls. But on the day of the auditions, she overhears some kids suggesting that she is not princess material. Tamika suddenly doesn't feel quite right enough to play a perfectly poised princess.
Publishers Weekly, May 2019
Booklist, February 2019
Kirkus Review, April 2019
2.7
K-3
AD550L
Keywords: Musicals -- Juvenile fiction; Schools -- Juvenile fiction; Self-confidence -- Juvenile fiction; Musicals -- Fiction; Schools -- Fiction; Self-confidence -- Fiction; Bullying -- Juvenile fiction